2011
DOI: 10.1111/j.2042-3292.2011.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐abdominal hypertension in horses

Abstract: Summary Intra‐abdominal hypertension (IAH) may lead to a multiple organ dysfunction syndrome associated with significant dysfunction of the cardiovascular, respiratory, renal, gastrointestinal and central nervous systems of human patients. A recent prospective multicentre epidemiological investigation in man concluded that IAH was associated with an increased risk of mortality in critically ill patients. In this review, we present current information pertaining to the potential clinical importance of IAH in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…The strength of the ventral midline closure during the immediate postoperative period is dependent on several variables that have been evaluated, such as suture gauge, suture closure pattern, suture closure technique, knot configuration, and surgeon experience 1,11,12,14 . The time during which horses are most at risk for development of acute incisional dehiscence has been shown to be the acute postoperative wound healing period, not during anesthetic recovery 21 . However, extreme stress and/or strain placed on an incision during recovery may contribute to alterations in wound healing and delayed incisional dehiscence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The strength of the ventral midline closure during the immediate postoperative period is dependent on several variables that have been evaluated, such as suture gauge, suture closure pattern, suture closure technique, knot configuration, and surgeon experience 1,11,12,14 . The time during which horses are most at risk for development of acute incisional dehiscence has been shown to be the acute postoperative wound healing period, not during anesthetic recovery 21 . However, extreme stress and/or strain placed on an incision during recovery may contribute to alterations in wound healing and delayed incisional dehiscence.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this early wound healing period is an important time for incisional support, which is clinically provided by abdominal bandages 2 . Dehiscence has been shown to occur more commonly during this early healing period vs acutely in recovery 21 . Horses that encounter incisional infections, have undergone previous celiotomy, or have significant trauma to the incision during recovery may benefit from the added support to the incision achieved through an external abdominal support bandage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indirect measurement techniques for estimating IAP have been extensively studied and validated in the human literature, as a highly correlated alternative to the more invasive, direct methods of assessment 8 . Several studies, however, have reported poor correlation between indirect IAP (ie, intravesicular 5 and intragastric 9,10 ) and direct IAP measurements in horses 6 . Previous reports in horses have indicated that direct intraperitoneal cannulation is the gold standard method for direct measurement of IAP in the horse, with proposed sampling locations including the right flank, left flank, and ventral abdomen 5,6,11 …”
Section: Introductionmentioning
confidence: 99%